2011
DOI: 10.1093/chrsci/49.4.292
|View full text |Cite
|
Sign up to set email alerts
|

Validated HPLC Method for Determination of Caffeine Level in Human Plasma using Synthetic Plasma: Application to Bioavailability Studies

Abstract: Several high-performance liquid chromatography (HPLC) methods have been described for the determination of caffeine in human plasma. However, none have been cross validated using synthetic plasma. The present study describes a simple and reliable HPLC method for the determination of the caffeine level in human plasma. Synthetic plasma was used to construct calibration curves and quality control samples to avoid interference by caffeine commonly present in donor's human plasma. After deproteination of plasma sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 17 publications
3
18
0
2
Order By: Relevance
“…The drawback of using buffer solution is to clog the column with the salt of buffer if there is no enough washing. Our study also compared with other previous reported work in terms of solvent consumption [20]. Chowdhury et al, reported that caffeine was separated after 20 min run at 1.0 mL which means each run could consume 20 mL [21], compared to our study, only 1.0 mL was consumed at 0.3 mL/min for each run.…”
Section: Results and Discussion Effect Of Sample Volume And Reconstitsupporting
confidence: 66%
“…The drawback of using buffer solution is to clog the column with the salt of buffer if there is no enough washing. Our study also compared with other previous reported work in terms of solvent consumption [20]. Chowdhury et al, reported that caffeine was separated after 20 min run at 1.0 mL which means each run could consume 20 mL [21], compared to our study, only 1.0 mL was consumed at 0.3 mL/min for each run.…”
Section: Results and Discussion Effect Of Sample Volume And Reconstitsupporting
confidence: 66%
“…The obtained R value is at 0.9911, whereas according to AOAC (2013), the suggested correlation coefficient is ≥ 0.99. That result fulfills linearity requirements and demonstrates that the test with the HPLC method has good linearity, therefore the linear regression equation can be used to determine levels of vitamin C in the samples (Alvi and Hammami 2011).…”
Section: Linearitysupporting
confidence: 59%
“…Validation Methods include: System suitability test, Linearity, and Precision (Alvi and Hammami, 2011).…”
Section: Study Coursementioning
confidence: 99%
“…The impedance response was recorded for each concentration by covering in a drop-like fashion the biosensors with an electron mediator solution of 5.0 × 10 −3 M of potassium hexacyanoferrate III, ( Interfering solutions of Myoglobin (Myo) and Immunoglobulin G (IgG) were prepared in PBS, with A concentration 6.0 × 10 −9 M, as IL-1β. Synthetic serum was also prepared according to [19] and consisted of NaCl (145 × 10 −3 M), KCl (4.5 × 10 −3 M), CaCl 2 (32.5 × 10 −3 M), MgCl 2 (0.8 × 10 −3 M), Urea (2.5 × 10 −3 M), and Glucose (4.7 × 10 −3 M) in aqueous solution.…”
Section: Solutionsmentioning
confidence: 99%